Anesthesia Approach for Nephrectomy in Full-Term Neonate with Suspected Wilms Tumor and Patent Foramen Ovale: A Case Report - Katarina, Ida; Otniel Adrians Labobar; I Putu Kurniyanta (HM Publisher, 2024)
Background: Nephrectomy for Wilms tumor presents a considerable challenge in pediatric anesthesia. This study aimed to describe the anesthesia approach for nephrectomy in a full-term neonate with suspected Wilms tumor and patent foramen ovale. Case presentation: A 25-day-old male neonate was referred with a longstanding intraabdominal mass present since birth. Echocardiography revealed a patent foramen ovale with a diameter of 2.7 mm and a left-to-right shunt. The patient also had a diagnosis of partial ileus obstruction, likely caused by the tumor's pressure on the left kidney. Preoperative fasting adhered to a